2016
DOI: 10.1016/s2095-3119(15)61105-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and trends for production and reproduction traits of a Landrace herd in China

Abstract: The objectives of this study were to estimate the genetic parameters and the breeding progress in a Landrace herd in China, and to predict the potential benefits by applying new breeding technology. Hereby, the performance records from a Landrace swine herd in China, composing over 33000 pigs born between 2001 and 2013, were collected on six economically important traits, average daily gain between 30-100 kg (ADG), adjusted backfat thickness at 100 kg (BF), adjusted days to 30 kg (D30), adjusted days to 100 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Reliable estimates of genetics parameters are essential in breeding programs as they lead to efficient pork production (Chimonyo et al, 2006;Zhang et al, 2016). During selection, not only a trait value is selected but an animal as a whole is considered.…”
Section: A N U S C R I P T Introductionmentioning
confidence: 99%
“…Reliable estimates of genetics parameters are essential in breeding programs as they lead to efficient pork production (Chimonyo et al, 2006;Zhang et al, 2016). During selection, not only a trait value is selected but an animal as a whole is considered.…”
Section: A N U S C R I P T Introductionmentioning
confidence: 99%
“…However, the genetic progress for litter traits in this study was much lower as compared with some pig populations selected in China or Thailand. For instance, a study on 6,363 sows in Chinese Landrace pigs during 2000 to 2012 reported an annual genetic gain of 0.08 piglets per litter per year for NBA [ 29 ]. Another study of total 3,109 Landrace and Yorkshire sows in Northern Thailand indicated that genetic trends were positive and significant for all traits during 1989 and 2013, that is, 0.16 for NBA, 0.12 for NW, and 1.23 for LWW [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because the ADG and D100 or D115 traits measure similar (although not identical) growth stage periods, it is expected that some significant SNPs will associate with more than one trait [ 34 ], while each trait will be associated uniquely with specific SNPs. Our results agree, in part, with previous QTL mapping and GWA studies.…”
Section: Discussionmentioning
confidence: 99%